Aerospace series. Bearing, spherical plain, in corrosion resisting steel with self-lubricating liner, low starting torque and low friction coefficient, elevated duty cycles under low oscillations at different operating conditions. Technical specification Part 3, (4th November 2019) - British Standards Institution,
No abstract available